Penerapan Media Permainan Ular Tangga Untuk Meningkatkan Kemampuan Mengenal Huruf Pada Peserta Didik - Miranda; Lukman Arsyad; Eka Apristian Pantu (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The ability to recognize letters is one of the important aspects in the development of early childhood literacy that needs to be developed through interesting learning activities that are in accordance with the characteristics of children. Based on the results of initial observations in Group A4 of PPAUDIT Lukmanul Hakim Gorontalo Regency, children's ability to recognize letters is still relatively low because most children have difficulty in recognizing, mentioning, and distinguishing letter shapes. This research aims to improve children's letter recognition skills through the application of snake and ladder game media. The method used is the Kemmis and McTaggart model Class Action Research (PTK) which is carried out in two cycles, including the planning stage, implementation of actions, observation, and reflection. The subjects of the study were 22 children. Data collection techniques are carried out through observation and documentation, while data analysis uses quantitative descriptive analysis. The results showed that children's ability to recognize letters increased significantly, from 36.36% in the pre-cycle stage to 72.72% in Cycle I and reached 100% in Cycle II. Thus, snake and ladder game media has been proven to be effective in improving literacy skills, learning motivation, and active involvement of children in learning.